2016
DOI: 10.1124/dmd.116.069344
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chromatin Structural Changes in Regulating Human CYP3A Ontogeny

Abstract: Variability in drug-metabolizing enzyme developmental trajectories contributes to interindividual differences in susceptibility to chemical toxicity and adverse drug reactions, particularly in the first years of life. Factors linked to these interindividual differences are largely unknown, but molecular mechanisms regulating ontogeny are likely involved. To evaluate chromatin structure dynamics as a likely contributing mechanism, age-dependent changes in modified and variant histone occupancy were evaluated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It should be noted that the ontogenic regulation of Cyp3a11 may not be solely PXR dependent, as it has been shown that district chromatin epigenetic signatures, such as increased permissive mark histone H3 lysine 4 di-methylation (H3K4me2) positively associates with the ontogenic increase of Cyp3a11 mRNA in developing mouse liver . During human liver development, the Cyp3a11 ortholog CYP3A4 gene locus is also extensively modified by the histone code, and the postnatal liver has reduced occupancy of repressive histone marks and higher occupancy of active histone marks compared to the fetal liver (Giebel et al, 2016). During aging, Cyp3a11 mRNA displays a consistent male-predominant pattern and decreases earlier in the livers of female mice than age-matched male mice (Fu et al, 2012).…”
Section: Pxr and Critical Time-windowsmentioning
confidence: 99%
“…It should be noted that the ontogenic regulation of Cyp3a11 may not be solely PXR dependent, as it has been shown that district chromatin epigenetic signatures, such as increased permissive mark histone H3 lysine 4 di-methylation (H3K4me2) positively associates with the ontogenic increase of Cyp3a11 mRNA in developing mouse liver . During human liver development, the Cyp3a11 ortholog CYP3A4 gene locus is also extensively modified by the histone code, and the postnatal liver has reduced occupancy of repressive histone marks and higher occupancy of active histone marks compared to the fetal liver (Giebel et al, 2016). During aging, Cyp3a11 mRNA displays a consistent male-predominant pattern and decreases earlier in the livers of female mice than age-matched male mice (Fu et al, 2012).…”
Section: Pxr and Critical Time-windowsmentioning
confidence: 99%
“…The age-dependent accumulation of changes in epigenetic modification states correlates with age-related changes in the expression of key metabolic enzymes, such as the cytochrome p450 (CYP) enzyme family (Giebel et al, 2016;Li et al, 2009) and may play a critical role in lifestage-dependent windows of susceptibility (de Magalhães et al, 2009). The diversity and abundance of expressed CYPs changes as a function of age (Hakkola et al, 1998;Parkinson et al, 2004;Stevens et al, 2003) and is an important determinant of inter-individual variability in xenobiotic metabolism (Hughes et al, 1996;Johnson, 2003;Tré luyer et al, 2001).…”
Section: Environmental Factors Influence the Epigenome Agementioning
confidence: 99%
“…Conversely, hepatic CYP3A4 expression is low at birth but increases through childhood and plateaus by adulthood (Stevens et al, 2003). Giebel et al (2016) attributed the ontogeny of CYP3A7 and 3A4 expression to changes in the balance of activating histone H3 lysine 4 trimethylation (H3K4me3) and repressive (H3K27me3) modification levels within the regulatory regions of these genes. The post-natal increase in CYP3A4 expression corresponds to an increase in H3K4me3 abundance, and thus a shift in the balance of H3K4me3/H3K27me3 in favor of gene expression after birth.…”
Section: Environmental Factors Influence the Epigenome Agementioning
confidence: 99%
“…For instance, histone modifications may participate in the CYP3A4 and CYP3A7 expression changes that occur in the embryonic period and in the first 2 years after birth. This mechanism seems to be important for CYP3A4, although other mechanisms may play a greater role in the regulation of CYP3A7 during ontogenesis [ 137 ].…”
Section: Mechanisms Of Cyp3a Regulationmentioning
confidence: 99%